Characterization of Gas Atomized Ni-Mn-Ga Powders. (2015) - Nilsén, F.; Aaltio, I.; Ge, Y.; Lindroos, T.; Hannula, S.P.
Abstract: Gas atomization is a well-known process for obtaining high quality metallic powders. It produces spherical high-density particles with a controllable particle size distribution. We used gas atomization to obtain two different Ni-Mn-Ga powders and investigated their microstructure, transformation temperatures and magnetic properties as well as the effects of heat treatment on those. The phase and magnetic transformation temperatures of the powders were considerably lower as compared to similar conventionally prepared alloys. Nevertheless, heat treatment of the atomized powder was found to recover the magnetic properties of the materials, probably by releasing the residual strains generated by the rapid solidification during the gas atomization process. Sintering of powders seemed to start at a significantly lower temperature when compared to the powder prepared by ball milling of bulk Ni-Mn-Ga-alloys.